Memories before the State : Postwar Peru and the Place of Memory, Tolerance, and Social Inclusion - Feldman, Joseph P. (Book collections on Project MUSE., 2021)
"Memories before the State examines the discussions and debates surrounding the creation of the Place of Memory, Tolerance, and Social Inclusion (LUM), a national museum in Peru that memorializes the country's internal armed conflict of the 1980s and 1990s. Emerging from a German donation that the Peruvian government initially rejected, the Lima-based museum project experienced delays, leadership changes, and limited institutional support as planners and staff devised strategies that aligned the LUM with a new class of globalized memorial museums and responded to political realities of the country's postwar landscape. Through an ethnographic study of this museum-in-progress, including vivid portrayals of LUM workers and representatives from victims' organizations, human rights NGOs, and the Peruvian armed forces, the book analyzes forms of authority that emerge as an official institution seeks to incorporate and manage diverse perspectives on recent violence"--